Trusted research environments are definitely about trust - Affleck, Paul (Journal of medical ethics, 2023)
In their highly topical paper, Graham et al argued that Trusted Research Environments (TREs) are not actually about trust because they reduce or remove ‘…the need for trust in the use and sharing of patient health data’. We believe this is fundamentally mistaken. TREs mitigate or remove some risks, but they do not address all public concerns. In this regard, TREs provide evidence for people to decide whether the bodies holding and using their data can be trusted. TREs may make it easier for people to trust but there is still a need for that trust.